Case Report: Reconstruction After Anterior Pubic Hemipelvectomy - Murphy, Benjamin; Thillainadesan, Tharsa; Robinson, Kerian; Clarke, Anita; Choong, Peter (Frontiers in Surgery, 2021)
We report on a case of a large grade 1 chondrosarcoma of the pelvis and its novel surgical resection with an anterior hemipelvectomy and reconstruction with an iliac crest graft. Surgical intervention is the mainstay treatment of pelvic chondrosarcomas. However there have been reports of concern regarding preventing pelvic visceral herniation and adequately reconstructing the pelvis. This report is unique within the literature and has yielded good functional outcomes whilst safely treating the malignancy.